2007
DOI: 10.1590/s1519-69842007000200012
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Blue-black Grassquits in central Brazil

Abstract: During the reproductive season Blue-black grassquit (Volatinia jacarina) males are found in clusters, wherein they exhibit a distinctive display that consists of repeated, vertical leaps while simultaneously producing a brief vocalization. The main objective of this study was to describe details of the species' reproductive behavior in a "Cerrado" area of central Brazil and compare these data with some studies carried out in other areas. The data obtained concerning different aspects of nesting, laying and hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
1
32
3
8
Order By: Relevance
“…Incubation performed only by the females and the less intensive participation of males in nestling provisioning has also been observed in the Grey-headed Tanager (skuTcH 1954). This pattern is different from that found for the Blue-black Grassquit, in which males share both incubation and nestling provisioning with the females (caRvalHo et al 2007). Notably, incubating females of the Red-crested Finch were reluctant to leave the nest when the observer approached it, allowing herself to be touched in the nest.…”
Section: Breeding Phenology and Nesting Behaviorcontrasting
confidence: 71%
See 1 more Smart Citation
“…Incubation performed only by the females and the less intensive participation of males in nestling provisioning has also been observed in the Grey-headed Tanager (skuTcH 1954). This pattern is different from that found for the Blue-black Grassquit, in which males share both incubation and nestling provisioning with the females (caRvalHo et al 2007). Notably, incubating females of the Red-crested Finch were reluctant to leave the nest when the observer approached it, allowing herself to be touched in the nest.…”
Section: Breeding Phenology and Nesting Behaviorcontrasting
confidence: 71%
“…First, nests of the Blue-black Grassquit Volatinia jacarina (Linnaeus, 1766) and the Grey-headed Tanager Eucometis penicillata (Spix, 1825) are in the shape of cups and are built mostly of rootlets. Although the nest walls are compact, they are so thin that eggs can be seen through them, and they lack any type of adornment (skuTcH 1954, caRvalHo et al 2007 (Swainson, 1838)), and the spots and blotches are often brownish and concentrated in the larger pole (Silver-beaked Tanager, Black-goggled Tanager, Ruby-crowned Tanager), or they can form a crown near the larger pole (Scarlet-rumped Tanager, Black-and-white Tanager) (euleR 1900, skuTcH 1950, 1954, PinTo 1953, HaveRscHmidT 1956, gReeney et al 2006, caRvalHo et al 2007, ingels 2007, gReeney & sHeldon 2008. This is another important distinctive characteristic of Coryphospingus, as these are the only tanagers that have completely white eggs.…”
Section: Nest Eggs and Hatchlings Characteristicsmentioning
confidence: 99%
“…However, our estimates of nest survival (26%) are in the range of those found for other emberizids in the cerrado region, both in natural habitats: Coal-crested Finch Charitospiza eucosma (20%; Diniz et al 2013), and in altered habitats: Blue-black Grassquits Volatinia jacarina (24%; Aguilar et al 2008), and Double-collared Seedeater Sporophila caerulescens (36%; Francisco 2006). Stripe-tailed Yellow-finch's nest success rates, nevertheless, were considerably lower than the observed for the Grassland Yellow-Finch Sicalis luteola breeding in Brachiaria-dominated pastures (47%; Freitas and Francisco 2012), and significantly higher than the observed for Blue-black Grassquits, also breeding in an altered habitat (>5%; Carvalho et al 2007). Such cases, however, apparently represent extreme values due to their discrepancies comparing to other studies in the cerrado region.…”
Section: Discussionmentioning
confidence: 61%
“…The males defend small territories during the breeding season, presenting a conspicuous, multi-modal display of repeated jumps from elevated perches, which are powered by wing-flapping, while exhibiting a white under-wing patch and vocalizing. Nests are built by each pair inside the male's territory and both male and female present parental care (Carvalho et al, 2007). The blue-black grassquit is socially monogamous (Almeida and Macedo, 2001), and recent studies have found a high rate of extra-pair fertilization (60% of chicks) for our study population (Carvalho et al, 2006).…”
Section: Study Animals and Housingmentioning
confidence: 86%
“…In central Brazil, where this study was conducted, these birds are migratory, arriving in the area each year starting in October, breeding from about November to April, after which they depart (Carvalho et al, 2007). Adult males exhibit plumage that varies from glossy black, during the breeding season, to black with brown patches, outside the breeding season (Aguilar et al, 2008), while females and juveniles have brown, inconspicuous plumage.…”
Section: Study Animals and Housingmentioning
confidence: 99%